A comparison of the effect of convection against diffusion in hemodynamics and cytokines clearance in an experimental model of septic shock - Herrera-Gutiérrez, Manuel Enrique; Seller Pérez, Gemma Luisa; Arias Verdú, Dolores; Granados, Maria M.; Domínguez, Juan M.; Navarrete, Rocío; Morgaz, Juan; Gómez Villamandos, Rafael (Wolters Kluwer, 2012)
BACKGROUND: Our aim was to define the efficacy of hemofiltration (convection) and hemodialysis (diffusion) in cytokine clearance and hemodynamic improvement in an experimental model of septic shock. METHODS: Shock was induced in 15 beagle dogs (weight 10Y15 kg) by infusion of 1 mg/kg of ultrapure Escherichia coli lipopolysaccharide diluted in 20 mL saline for 10 minutes. Five animals were followed without interventions (controls), five animals were treated with convection (100 mL kgj1 hj1) for 6 hours, and five animals were treated with diffusion (100 mL kgj1 hj) for 6 hours. RESULTS: All subjects in the control group died during the study, whereas all treated subjects survived. Mean arterial pressure, cardiac output, systolic variability volume, systemic vascular resistances, dPMax, and pulmonary compliance improved in treated subjects. However, the differences in mean arterial pressure and cardiac output were significant only in the convection group and not in the diffusiontreated group. Tumor necrosis factor > rose equally in all groups and decreased only in treated subjects. Interleukin 6 rose in the three groups but decreased only in the convection group and remained unchanged in the control and diffusion groups. CONCLUSION: Convection and diffusion improved survival and hemodynamic parameters in a septic shock model. Improvement was more pronounced with convection, a difference that may be explained by convective clearance of cytokines.
Keywords: Citoquinas; Enfermedades - Modelos animales; Hemodinámica; Cytokines; Convection; Disease models; Hemidynamics